The true identity of Dixa modesta Johannsen (Diptera: Dixidae) resolved: synonymy of Dixa similis Johannsen, designation of the Dixa ubiquita species group, and description of three new eastern Nearctic species - Moulton, John K. (Zootaxa, 2017)
Examination of the lectotype male of Dixa modesta Johannsen revealed this species has a confused taxonomic history. It was discovered that Dixa modesta and Dixa similis Johannsen are based on the same nominal species, the former having priority. As a result, Dixa similis falls into synonymy with Dixa modesta (syn. nov.). The species long considered to correspond to the latter (since 1966 if not earlier), i.e., Dixa modesta sensu Peters, comprises three distinct sibling species based on a combination of morphological and molecular evidence. Adults of each sibling are described herein (D. elkmontensis sp. nov., D. ubiquita sp. nov., D. vockerothi sp. nov.), and the D. ubiquita species group is proposed to include them. Morphological diagnoses and a dichotomous key are provided to separate adult males of the D. ubiquita group from those of all other Nearctic species and each other, respectively. Molecular diagnoses are provided to allow identification of any life stage of these three siblings. Updated life history and distributional data are also reported for each sibling.